Measuring park accessibility for pedestrian in Manhattan, Kansas - Alahmary, Ali (Kansas State University, 2019)
Here in Manhattan, some areas do not qualify for pedestrian users. It implies that the people who live in those areas do not have an equal opportunity to access the parks around them. Most of the park accessibility measurements do not consider the quality of the trip or the walking trip as a major factor for measuring accessibility to public amenities. In this research, we measure the quality of park distribution for pedestrian use in Manhattan, KS. The methodology of the study uses three variables to measure the park distribution: the number of opportunities (Parks) within cut off distance of 800m, the quality of the parks, and the quality of the walking trip to the parks based on the existence of the sidewalk in the city. These variables test the hypotheses: If the people (race, age, and homeownership) of Manhattan, KS have difficulty accessing all parks by walking, then it showed a lack of efficiency of the parks' distribution for pedestrians. The results showed that the difference between the racial groups is very low in terms of accessibility, which indicates a low degree of inequity. For the homeownership groups, the difference between the groups has shown an advantage for the renter group in all the accessibility measurements. For the age groups, the result in all the accessibility measurements favored the age group of 5 to 19 years old. Overall the results show that the differences between groups are statistically significant, but still small in term of equity.
Keywords: Accessibility; ParkEquity